Can Social Advertising And Internet Meme Enhance Consumer Trust And Satisfaction? - Latif, Fakhruriyah Agustin; Suryani, Tatik (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2024)
Despite some companies using social advertising and internet meme on social media, less research focuses on the impact of both brand image and also its effect on customers trusts and satisfaction. In fashion industry in Indonesia some of companies used social advertising and internet meme for enhanching their brand image. This research focus on Zoya which produce Moslem wear and in the top position in the market, but recently many new competitor entrants in this market. The objective of this research is to examine the effect of social advertising and internet memes on brand image, and the effect of brand image on customer trust and customers satisfaction. The research was designed by survey which. Involved 232 respondents. Data were analyzed using the Partial Least Square method. The research found that social advertising and internet memes have a positive significantly effect on Brand Image, and Brand Image has positive significantly affect consumer trust and satisfaction.The implication of the research is that company should manage internet meme and social advertising effectively and always improve the content fit in the trend and customer expectation.